Motivasi dan Sikap Terhadap Kunjungan Ulang Wisatawan Lokal ke Curug Leuwi Hejo Kabupaten Bogor - Nadiya Fithri Fathima; Siti Komsiah; Euis Puspita Dewi; Nana Trisnawati; Maya Syafriana Effendi; Rilla Sovitriana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this study is to find out how far the relationship between motivation and attitudes of tourist towards decision to revisit. The research method used in this research is descriptive analysis with a quantitative approach. The technique used in determining the sample in this study was non-probability sampling with accidental sampling method. The questionnaire used a Likert scale with 23 items that validity had been tested. Instrument reliability was tested using Cronbach's Alpha and all variables have reliability value of >0.6. The results of the multiple linear regression analysis showed that there was a positive influence of tourist motivation on the intention to revisit Curug Leuwi Hejo